Multimodal Optical Imaging to Investigate Spatiotemporal Changes in Cerebrovascular Function in AUDA Treatment of Acute Ischemic Stroke - Wang, Han-Lin; Chen, Jia-Wei; Yang, Shih-Hung; Lo, Yu-Chun; Pan, Han-Chi; Liang, Yao-Wen; Wang, Ching-Fu; Yang, Yi; Kuo, Yun-Ting; Lin, Yi-Chen; Chou, Chin-Yu; Lin, Sheng-Huang; et al. (Frontiers in Cellular Neuroscience, 2021)
Administration of 12-(3-adamantan-1-yl-ureido)-dodecanoic acid (AUDA) has been demonstrated to alleviate infarction following ischemic stroke. Reportedly, the main effect of AUDA is exerting anti-inflammation and neovascularization via the inhibition of soluble epoxide hydrolase (sEH). However, the major contribution of this anti-inflammation and neovascularization effect in the acute phase of stroke is not completely elucidated. To investigate the neuroprotective effects of AUDA in acute ischemic stroke, we combined laser speckle contrast imaging (LSCI) and optical intrinsic signal imaging (OISI) techniques with the implantation of a lab-designed cranial window. Forepaw stimulation was applied to assess the functional changes via measuring cerebral metabolic rate of oxygen (CMRO2) that accompany neural activity. The rats that received AUDA in the acute phase of photothrombotic ischemia stroke showed a 30.5% ± 8.1% reduction in the ischemic core, 42.3% ± 15.1% reduction in the ischemic penumbra (p < 0.05), and 42.1% ± 4.6% increase of CMRO2 in response to forepaw stimulation at post-stroke day 1 (p < 0.05) compared with the control group (N = 10 for each group). Moreover, at post-stroke day 3, increased functional vascular density (FVD) was observed in AUDA-treated rats (35.9% ± 1.9% higher than that in the control group, p < 0.05). At post-stroke day 7, a 105.4% ± 16.4% increase of astrocytes (p < 0.01), 30.0% ± 10.9% increase of neurons (p < 0.01), and 65.5% ± 15.0% decrease of microglia (p < 0.01) were observed in the penumbra region in AUDA-treated rats (N = 5 for each group). These results suggested that AUDA affects the anti-inflammation at the beginning of ischemic injury and restores neuronal metabolic rate of O2 and tissue viability. The neovascularization triggered by AUDA restored CBF and may contribute to ischemic infarction reduction at post-stroke day 3. Moreover, for long-term neuroprotection, astrocytes in the penumbra region may play an important role in protecting neurons from apoptotic injury.